1971
DOI: 10.1111/j.1471-0528.1971.tb00201.x
|View full text |Cite
|
Sign up to set email alerts
|

Nuchal Encirclement by the Umbilical Cord

Abstract: Nuchal encirclement by the umbilical cord is a common cause of fetal distress, and may result in neonatal depression and acidaemia. Severe irregularity of the fetal heart gives prolonged warning of the condition. The temporal relationship of transient episodes of bradycardia to uterine contractions is not helpful in differentiating cord entanglement from other causes of fetal hypoxaemia. Tipton, R. H. (1971): M.D. Thesis, Sheffield University. Tipton, R. H., and Shelley, T. (1971): Journal of Obstetrics and Gy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

1973
1973
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
0
5
1
Order By: Relevance
“…In this study we were unable to demonstrate significant elevation of MDA or OHP levels in the cord blood of infants with loose‐nuchal cord: rather a significant decrease was observed. This could explain the differences observed in previous studies 5,8,19 where the severity of nuchal cord tightness was not stated. This group was also noted to have a significantly higher mean AFI than either the tight‐ or non nuchal cord groups.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…In this study we were unable to demonstrate significant elevation of MDA or OHP levels in the cord blood of infants with loose‐nuchal cord: rather a significant decrease was observed. This could explain the differences observed in previous studies 5,8,19 where the severity of nuchal cord tightness was not stated. This group was also noted to have a significantly higher mean AFI than either the tight‐ or non nuchal cord groups.…”
Section: Discussioncontrasting
confidence: 56%
“…A nuchal cord is associated with altered oxygen saturation in umbilical arterial blood and with increased frequency of fetal distress in labour 6,7 . A direct relation has been demonstrated between fetal acid‐base balance and the subsequent neonatal course 8 . However, there are no publications concerning possible association between oxygen‐free radical activity and nuchal cord entanglement.…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings have been reported by other centers [3,18,21]. In an attempttoreduce this number of antepartum fetal deaths we decided to monitor the fetal heart rate in patients admitted prior to labor (during the first 24 hours after admission).…”
Section: Introductionmentioning
confidence: 78%
“…The presence of a nuchal cord has been associated with many different factors in the mother, fetus, cord, placenta and labor and with a less favorable fetal outcome; however, the majority of these studies are case reports or small series. There are reports of associations with breech presentation, right‐sided fetal position, a male fetus, increased fetal activity, reduced fetal movements30, a long length and less vascular coiling of the cord31, 32, abnormal umbilical artery Doppler findings33, abnormal ductus venosus velocity waveforms34, a posterior placenta35, induction of labor4, variable decelerations of the fetal heart rate4, 14, 36, 37, meconium‐stained amniotic fluid4, 14, 37, 38, shoulder dystocia39, operative vaginal delivery14, emergency lower segment Cesarean section38, IUGR7, 8, low Apgar scores4, 14, 17, 40, increased neonatal unit admission38, need for resuscitation4, umbilical artery acidemia14, 41, neonatal hypovolemic shock42, neonatal anemia10, dural sinus dilatation43, stillbirth17, 44, 45, poor neurodevelopmental performance at 1 year3 and cerebral palsy46, 47. Despite these reports, a nuchal cord is usually associated with a normal neonatal and maternal outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The present study found that women with a nuchal cord did not have a significantly higher risk of emergency Cesarean section or of Cesarean section for fetal distress. Nuchal cord has been consistently associated with an increased rate of fetal heart rate abnormalities, so there has been concern that this might lead to a higher chance of Cesarean section for presumed fetal distress4, 14, 36, 37. We found no such association in the present study, but our sample size was relatively small compared to other studies that have found such an association38.…”
Section: Discussionmentioning
confidence: 99%